The Analysis Speech Acts of Donald Trump’s Speech - Febriana, Sonya Widya; Fajariah, Muziatun Fajariah (PROJECT (Professional Journal of English Education), 2018)
This research is entitled the analysis speech acts of Donald Trump’s speech. The study analyze the speech acts of President Donald Trump’s speech. The speeches used as the data are taken from White House online on September until October 2017 in USA. Moreover, the researcher focused on speech act of illocutionary acts. In this study the research used theory from Searle. From Donald Trump's speech, the researcher found 7% Declarative, 18% Representative, 31% Expressive, 29% commissive, and 15% Directive. The result showed that President Donald Trump’s more on sentence expressive. Analysis speech act help in the interpretation of the message in the selected speech.Keywords:  Speech act, types of speech acts